1997
DOI: 10.1006/anbo/79.5.505
|View full text |Cite
|
Sign up to set email alerts
|

Early Scion/Stock Junction in Compatible and Incompatible Pear/Pear and Pear/Quince Grafts: a Histo-cytological Study

Abstract: A comparative histo-cytological study of compatible and incompatible pear/pear and pear/quince grafts, grown in a glasshouse, was carried out on unions collected from day 1 to day 22 after budding (DAB). Successive steps leading to the graft junction were studied. Adhesion between the two partners was observed along the inner bark tissues (phloem and cambium) just 24 h after budding, while a necrotic layer appeared at the graft interface. The first cell divisions were observed 3 DAB. In the inner bark interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
2
14
0
5
Order By: Relevance
“…Gur et al (1968) postulate that in the pear and quince grafting a possible mechanism for this so-called localized incompatibility has been proposed, involving the potential toxic effects of prunasin, a cyanogenic glycoside. According to this hypothesis prunasin that is present in the bark tissues of quince rootstocks, would ascend into the pear scion where it is hydrolyzed by βglicosidases, releasing cyanide which is toxic to cambial cells causing therefore necrosis of cell tissue on the scar (Ermel et al, 1997). The necrosis reduces the transport of water and nutrients through the graft union.…”
Section: Introductionmentioning
confidence: 99%
“…Gur et al (1968) postulate that in the pear and quince grafting a possible mechanism for this so-called localized incompatibility has been proposed, involving the potential toxic effects of prunasin, a cyanogenic glycoside. According to this hypothesis prunasin that is present in the bark tissues of quince rootstocks, would ascend into the pear scion where it is hydrolyzed by βglicosidases, releasing cyanide which is toxic to cambial cells causing therefore necrosis of cell tissue on the scar (Ermel et al, 1997). The necrosis reduces the transport of water and nutrients through the graft union.…”
Section: Introductionmentioning
confidence: 99%
“…Errea et al (2001) used contingency tables, but no statistical differences were found and there was reduction in validity of the test. Correspondence analysis seems to offer a better procedure to discriminate compatible combinations from incompatible combinations (Ermel et al, 1997). It is based on c 2 transformation and produces dimensions that represent the c 2 distances (Lebart et al, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…5C shows that prolific callus cells make the union line narrow. According to Ermel et al (1997), cell necrosis and discontinuity of vascular connections at the union are the main indicators of incompatibility. Gebhardt and Feucht (1982) reported a high quantity of phenols above the union as a cause of graft incompatibility in Prunus species.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise Ermel et al (1997) showed that cell necrosis and lack of vascular connection continuity in graft union was the manifest symptoms of graft incompatibility. Errea et al (1994a) reported that insufficient differentiation of callus cells in some areas of graft union affected the newly formed xylem and phloem activity.…”
Section: Histologic Analysismentioning
confidence: 99%